2004
DOI: 10.1093/jpepsy/jsh050
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of an Integrated Health Education Program in an Urban School System: Planet Health

Abstract: Planet Health was feasible and acceptable in a participatory research model involving a public school-university partnership, and it was also sustainable independent of the research effort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(68 citation statements)
references
References 31 publications
4
60
0
4
Order By: Relevance
“…Facilitators were support from a technical unit (including training) and access to resources (materials and funding: all resources were provided free for the school through provincial funding). These operational factors have been identified consistently in the school health literature (31,34,35,(51)(52)(53)(54)(55)(56) . Durlak and DuPre characterized leadership, access to resources (funding), time and loss of momentum due to competing demands in their broader implementation framework as delivery system factors (21) .…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Facilitators were support from a technical unit (including training) and access to resources (materials and funding: all resources were provided free for the school through provincial funding). These operational factors have been identified consistently in the school health literature (31,34,35,(51)(52)(53)(54)(55)(56) . Durlak and DuPre characterized leadership, access to resources (funding), time and loss of momentum due to competing demands in their broader implementation framework as delivery system factors (21) .…”
Section: Discussionmentioning
confidence: 72%
“…Planning for the state-wide scale-up of the Child and Adolescent Trial for Cardiovascular Health (CATCH) in Texas (29) identified the importance of factors such as networks, cost, training, ongoing support, targeted approaches and the importance of both supporting and examining implementation after adoption. However, we know relatively little about factors that influence implementation of school HE interventions after scale-up in real-world settings; this deficit must be overcome to enhance the effectiveness of target interventions (33)(34)(35)(36)(37) .…”
mentioning
confidence: 99%
“…The school is a primary social environment that can reach a significant proportion of youths (Baker, Dilly, Aupperlee, & Patil, 2003) and acts as a site for prevention and promotion of multiple behaviour interventions (Deschesnes, et al, 2003). Examples of three successful intervention programs include: the Coordinated Approach to Child Health (CATCH) (Nader et al, 1999), Planet Health (Wiecha et al, 2004) and Not-On-Tobacco (NOT) (Horn, Dino, Kalsekar, & Mody, 2005). Some common success elements across these three programs are inclusion of multiple stakeholders, familiarity with the culture of the school, flexibility for local adaptation, building effective partnerships and use of theory (Franks et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The Diffusion of Innovations Theory, and its adaptations, has been applied across several health-and nutritionrelated studies. 35,36 …”
Section: Effectiveness Researchmentioning
confidence: 99%